Absorption and metabolism of vitamin D in health and in gastrointestinal tract diseases - E. A. Pigarova; L. К. Dzeranova; D. A. Yatsenko (Ожирение и метаболизм, 2022)
Over the past decades, we have witnessed many remarkable advances in understanding the impact of vitamin D on human health. There is an exponential growth of new data covering both the fundamental biology of vitamin D and the clinical implications of deficiency and the effects of vitamin D supplementation. This literature review has been prepared to combine and interpret the current scientific evidence on the mechanisms of vitamin D absorption, with a focus on vitamin D absorption through the apical membrane of enterocytes in various pathologies of the gastrointestinal tract. Reviewed studies have identified some distinctive aspects of vitamin D bioavailability that should be considered in the treatment or prevention of vitamin D deficiency in patients with malabsorption syndromes, especially in the active phase of the disease. Moreover, recent in vivo experiments and in vitro studies have demonstrated that vitamin D absorption is not a simple diffusion process as previously thought, but rather a mechanism that also involves multiple membrane transporters. Maintaining or improving vitamin D intake through diet or increased sun exposure is problematic, so oral supplementation may be an effective and safe approach to improving vitamin D status. Vitamin D3 is the recommended form for both prevention and treatment of vitamin D deficiency, which is associated with more stable pharmacokinetics. Vitamin D absorption is improved when vitamin D is taken with a small amount of fat-containing food and medium chain triglycerides. In malabsorption syndromes, it is optimal to increase the general population doses of vitamin D by 2–3 times both for prevention and for the treatment of deficiency and insufficiency. While vitamin D deficiency is more common among people with gastrointestinal disease, data have not been able to establish whether the relationship is causal or the result of intestinal inflammation and malabsorption syndrome. However, owing to the understanding of the mechanisms of action of vitamin D, there is evidence that its deficiency can be directly related to the severity of the disease, and partly to the etiology or pathogenesis of the disease itself.